KEPATUHAN INDONESIA PADA AGREEMENT ON TRADE RELATED ASPECTS OF INTELLECTUAL PROPERTY RIGHTS STUDI KASUS: PEMALSUAN PRODUK FASHION TAHUN 2010-2015 - Vita Fulla Mayliya; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2019)
The detrimental effect of counterfeiting was the main factor of the WTO-TRIPs Agreement establishment. TRIPs Agreement has been regarded as the international intellectual property rights (IPRs) regime which its important role is providing minimum standards of the intellectual property rights protection and enforcement. Fashion counterfeiting has been one of the phenomena that infringes most of IPRs, particularly on trademarks. It requires global consciousness due to its undetected nature and negative impacts, especially for Indonesia. Indonesia is one of the largest producers in fashion industry. Ironically, it has experienced major counterfeiting problems in its respective regions. Indonesia itself is considered to have potential contribution to the counterfeit fashion trade. However, Indonesia is committed to comply with TRIPs’ regulations due to the single undertakings principle that was agreed upon joining WTO’s membership. This research aims to explain and analyze the influence of TRIPs Agreement on Indonesian compliance in addressing fashion product counterfeiting in 2010-2015. The qualitative method with Rationalist-Functionalism approaches are being used to answer the research question. The result of the analysis is TRIPs Agreement has influenced Indonesian compliance in addressing fashion product counterfeiting in 2010-2015 by: (1) taking into account the relevance and realization of TRIPs Agreement function as international IPRs regime towards counterfeiting issue; (2) affecting Indonesian perception on the importance to provide adequate trademarks protection and enforcement for its fashion industri; and (3) providing economic incentives in the form of reputation, market access, and investation.